Cuff Leak Test and Airway Obstruction in Mechanically Ventilated ICU Patients (COMIC): a pilot randomised controlled trial protocol. Issue 7 (19th July 2019) - Lewis, Kimberley; Culgin, Sarah; Jaeschke, Roman; Perri, Dan; Marchildon, Corry; Hassall, Kelly; Piraino, Thomas; Thabane, Lehana; Almubarak, Yousef; Alshahrani, Mohammed S; Rochwerg, Bram; Baw, Bandar; et al.
Abstract : Introduction: Endotracheal intubation and invasive mechanical ventilation are lifesaving interventions that are commonly performed in the intensive care unit (ICU). Laryngeal oedema is a known complication of intubation that may cause airway obstruction in a patient on extubation. To date, the only test available to predict this complication is the cuff leak test (CLT); however, its diagnostic accuracy and utility remains uncertain. Herein, we report the protocol for the CuffLeak and AirwayObstruction in MechanicallyVentilated ICU Patients (COMIC) pilottrial. Methods and analysis: This will be a multicentred, pragmatic, pilot randomised controlled trial (RCT). We will enrol 100 mechanically ventilated patients in the ICU who are deemed ready for extubation. We will exclude patients at a high risk of laryngeal oedema. All enrolled patients will have a CLT done before extubation. In the intervention arm, the results of the CLT will be communicated to the bedside physician, and decision to extubate will be left to the treating team. In the control arm, respiratory therapist will not communicate the results of the CLT to the treating physician, and the patient will be extubated regardless of the CLT result. Randomisation will be done in a 1:1 allocation ratio, stratified by size of the endotracheal tube and duration of invasive mechanical ventilation. Although we will examine all clinical outcomes relevant for the future COMIC RCT, the primary outcomes of the COMIC pilottrial will be feasibility outcomes including: consent rate, recruitment rate and protocol adherence. Clinical outcomes include postextubation stridor, reintubation, emergency surgical airway, ICU mortality, in hospital mortality, duration of mechanical ventilation and ICU length of stay in days. Ethics and dissemination: The Hamilton Integrated Research Ethics Board, Imam Abdulrahman Bin Faisal University Institutional Review Board and Bioethical Commission of the Jagiellonian University approved this study. The trial results will be disseminated via publication in peer-reviewed journals. Trial registration number: NCT03372707 .